Shifting Perspectives in Tribal Studies From an Anthropological Approach to Interdisciplinarity and Consilience - Behera, Maguni Charan (Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together multidisciplinarity, desirability and possibility of consilience of borderline studies which are topically diverse and methodologically innovative. It includes contemporary tribal issues within anthropology and other disciplines. In addition, the chapters underline the analytical sophistication, theoretical soundness and empirical grounding in the area of emerging core perspectives in tribal studies. The volume alludes to the emergence of tribal studies as an independent academic discipline of its own rights. It offers the opportunity to consider the entire intellectual enterprise of understanding disciplinary and interdisciplinary dualism, to move beyond interdisciplinarity of the science-humanities divide and to conceptualise a core of theoretical perspectives in tribal studies. The book proves an indispensable reference point for those interested in studying tribes in general and who are engaged in the process of developing tribal studies as a discipline in particular. .